The influence of institutionally embedded ownership on Anglo-American corporate governance migration into emerging economy IPO firms - Bruce Hearn; Lars Oxelheim; Trond Randøy (Research Institute of Industrial Economics (IFN), 2017)
We argue that the corporate governance of emerging economy IPO firms is influenced by firm-specific institutionally embedded block ownership groups. Applying an extended institutional logic perspective and using a mixed-effects ordered probit model, our findings from 190 IPO-firms from 22 African countries 2000-2016, support the notion that five major block owner categories (corporate, private equity, non-executive, business group, state) exerts very different influence on African firms' degree of adoption of Anglo-American corporate governance measures. We find that the influence from the various block owner groups is significantly moderated by institutional quality and tribalism, but to different degrees and directions across block owner groups. Our contextually embedded firm-specific results support the criticism of a one-hat-fits-all global and uniform corporate governance model.
Keywords: G23; G38; M12; M14; M16; 330; IPO; Corporate Governance Practice; Institutional Theory; Africa; Emerging Economies